ANALISIS PENYEBAB INSIDEN PASIEN JATUH DI RAWAT INAP RS. Y DI KOTA PADANG - Dwi Novilolita; Yuniar Lestari; Hardisman Hardisman (Universitas Putera Batam, 2019)
Patient falls incident are unplanned incident with or without injuries in the inpatient unit. Based on minimum service standards, the fall incident which is part of patient safety is expected as 0%. Based on preliminary data from the Quality and Risk Management Committee in